2007
DOI: 10.1073/pnas.0701877104
|View full text |Cite
|
Sign up to set email alerts
|

Control of specificity and magnitude of NF-κB and STAT1-mediated gene activation through PIASy and PIAS1 cooperation

Abstract: NF-B and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 21 publications
4
66
0
Order By: Relevance
“…It has also been shown that genes activated by RelA dimers can be negatively regulated by the E3 ligase PIAS1, a member of the protein inhibitor of activated STAT (PIAS) family [45]. Pias1 −/− mice showed significantly elevated RelA binding to κB sites in genes that also showed hyper-expression [46]. A second line of research provided evidence that promoter-bound RelA and cRel can be phosphorylated by IKK activity thereby catalyzing their degradation [47].…”
Section: Kinetic Control Of the Canonical Pathwaymentioning
confidence: 95%
“…It has also been shown that genes activated by RelA dimers can be negatively regulated by the E3 ligase PIAS1, a member of the protein inhibitor of activated STAT (PIAS) family [45]. Pias1 −/− mice showed significantly elevated RelA binding to κB sites in genes that also showed hyper-expression [46]. A second line of research provided evidence that promoter-bound RelA and cRel can be phosphorylated by IKK activity thereby catalyzing their degradation [47].…”
Section: Kinetic Control Of the Canonical Pathwaymentioning
confidence: 95%
“…PIAS1 and PIASy do not inhibit expression of all ISGs (21,36,37). It is likely that ISGs are divided into distinct groups, partly according to different types of negative regulation under which they are controlled.…”
Section: Discussionmentioning
confidence: 99%
“…LXXLL Motif in the SAP Domain Is Not Involved in the Inhibition of Type I IFN Transcription-PIASy has been reported to inhibit IFN␥-mediated activation of IFN stimulated genes (ISGs) by preventing STAT1-dependent activation of ISRE promoter activity (37,45). Although type I IFN transcription is initially activated by IRF3/7, it is further enhanced by the subsequent IFN-positive feedback loop activated by STAT1 and the ISGF3 complex (46 -48).…”
Section: Piasy Negatively Regulates Virus-induced Type I Ifnmentioning
confidence: 99%
See 2 more Smart Citations